Answer:
= 2 (sec (x/2) - 2sec³(x/2) + sec⁵(x/2) ) + C
3 5
Explanation:
∫sec(x/2) tan⁵(x/2) dx
apply u substitute u = x/2
= ∫sec(u) tan⁵(u) * 2du
= 2 * ∫sec(u) tan⁴(u) tan(u) du
= 2 * ∫sec(u) (tan²(u))² tan(u) du
= 2 * ∫sec(u) (-1 + sec²(u))² tan(u) du
apply u substitute v = sec(u)
= 2 * ∫(-1 + v²)² dv
expand
= 2 * ∫1 - 2v² + v⁴ dv
sum
= 2 (v - 2v³ + v⁵ )
3 5
substitute it back
= 2 (sec (x/2) - 2sec³(x/2) + sec⁵(x/2) )
3 5
add constant to the solution.
= 2 (sec (x/2) - 2sec³(x/2) + sec⁵(x/2) ) + C
3 5